Pengembangan Media Visual Interaktif IPAS Kelas V Berbasis Canva di UPTD SDN 96 Barru: Penelitian - Abdul Wahid; Nur Afni; Hamra Amelia; Nur Fadilla; Reli Citra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The reliance of elementary school teachers on conventional learning media and the limited use of interactive learning media in Science or Integrated Science (IPAS) learning form the background of this study. This research aimed to develop a Canva-based interactive visual learning media that is feasible and practical for IPAS learning and to describe its implementation in the classroom. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages, and was supported by a descriptive qualitative approach during the implementation stage. The media development process involved expert validation to assess feasibility in terms of content accuracy, visual appearance, interactivity, and language clarity. Practicality testing was conducted through teacher and student responses after the media was implemented in learning activities. The results indicated that the developed Canva-based interactive visual media achieved a very high level of feasibility and was categorized as highly practical. In addition, the use of this media supported active student engagement during the learning process. Therefore, the Canva-based interactive visual learning media is considered feasible and practical for use in elementary school IPAS learning.